Advances and Applications of Oxidized van der Waals Transition Metal Dichalcogenides - Brian S. Y. Kim; Tien Dat Ngo; Yasir Hassan; Sang Hoon Chae; Soon‐Gil Yoon; Min Sup Choi (Advanced Science)
Abstract The surface oxidation of 2D transition metal dichalcogenides (TMDs) has recently gained tremendous technological and fundamental interest owing to the multi‐functional properties that the surface oxidized layer opens up. In particular, when integrated into other 2D materials in the form of van der Waals heterostructures, oxidized TMDs enable designer properties, including novel electronic states, engineered light‐matter interactions, and exceptional‐point singularities, among many others. Here, the evolving landscapes of the state‐of‐the‐art surface engineering technologies that enable controlled oxidation of TMDs down to the monolayer‐by‐monolayer limit are reviewed. Next, the use of oxidized TMDs in van der Waals heterostructures for different electronic and photonic device platforms, materials growth processes, engineering concepts, and synthesizing new condensed matter phenomena is discussed. Finally, challenges and outlook for future impact of oxidized TMDs in driving rapid advancements across various application fronts is discussed.